Effects of Applied Potential and Reactants to Hydrogen-Producing Biocathode in a Microbial Electrolysis Cell - Lim, Swee Su; Kim, Byung Hong; Li, Da; Feng, Yujie; Daud, Wan Ramli Wan; Scott, Keith; Yu, Eileen Hao (FRONTIERS MEDIA SA, 2018)
Understanding the mechanism of electron transfer between the cathode and microorganisms in cathode biofilms in microbial electrolysis cells (MECs) for hydrogen production is important. In this study, biocathodes of MECs were successfully re-enriched and subjected to different operating parameters: applied potential, sulfate use and inorganic carbon consumption. It was hypothesized that biocathode catalytic activity would be affected by the applied potentials that initiate electron transfer. While inorganic carbon, in the form of bicarbonate, could be a main carbon source for biocathode growth, sulfate could be a terminal electron acceptor and thus reduced to elemental sulfurs. It was found that potentials more negative than -0.8 V (vs. standard hydrogen electrode) were required for hydrogen production by the biocathode. In additional, a maximum hydrogen production was observed at sulfate and bicarbonate concentrations of 288 and 610 mg/L respectively. Organic carbons were found in the cathode effluents, suggesting that microbial interactions probably happen between acetogens and sulfate reducing bacteria (SRB). The hydrogen-producing biocathode was sulfate-dependent and hydrogen production could be inhibited by excessive sulfate because more energy was directed to reduce sulfate (E degrees SO42- /H2S = -0.35 V) than proton (E degrees H+/H-2 = -0.41 V). This resulted in a restriction to the hydrogen production when sulfate concentration was high. Domestic wastewaters contain low amounts of organic compounds and sulfate would be a better medium to enrich and maintain a hydrogen-producing biocathode dominated by SRB. Besides the risks of limited mass transport and precipitation caused by low potential, methane contamination in the hydrogen-rich environment was inevitable in the biocathode after long term operation due to methanogenic activities.